(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
As Orthopaedic surgeons, we are trained to approach patient problems in a systematic and evidence-based manner. We rely on algorithms, guidelines, and treatment protocols to guide our decisions, and we strive to achieve consistent outcomes across patients. However, as we all know, biology is not mathematics. While it is important to have a structured approach to patient care, we must also recognize the importance of individualized treatment.